A Comparative Study of the Temperature Coefficient Q10 in Hibernating Ground Squirrels Urocitellus undulatus and Cooled Rats of Different Ages - Zakharova, N. M.; Tarahovsky, Yu. S.; Khrenov, M. O. (Journal of evolutionary biochemistry and physiology, 2024)
The temperature coefficients of heart rate ( Q10 HR ) or oxygen consumption ( Q10 Ox ) were analyzed upon arousal from natural hibernation in long-tailed ground squirrels Urocitellus undulatus and during the rewarming of artificially precooled adult rats and rat pups. The Q10 Ox value was calculated using a standard equation, whereas for calculating Q10 HR , the equation was empirically modified to track changes in this parameter over a wide range of body temperatures ( T b ). It was found that during the initial period of arousal from torpor, at T h ≤ 10°C, ground squirrels demonstrated a sharp increase in the temperature coefficients up to Q10 HR = 40–50 and Q10 Ox = 6–7. Even higher values of Q10 HR (>100) were recorded at the onset of rewarming of rat pups, although they had a low level of Q10 Ox (1.2). Adult rats could not tolerate cooling below 16°C and demonstrated a moderate variability of both Q10 HR = 2.0–4.0 and Q10 Ox = 2.0–2.2. During the recovery of normal T b , the Q10 HR values in all animals approximated to ~2.0, as predicted by the van’t Hoff–Arrhenius rule for chemical reactions in both living and inanimate nature. We assume that high values of Q10 HR and Q10 Ox , detected in the early period of ground squirrel’s arousal from hibernation, may indicate the functioning of adaptive processes aimed at accelerating body warming. Resistance to cooling and a high Q10 HR in rat pups may suggest the rudimentary adaptability to hibernation in the juvenile period of rats as representatives of the order Rodentia, which also includes such natural hibernators as ground squirrels.